A Unity Power Factor Boost Rectifier with a Predictive Capacitor Model for High Bandwidth DC Bus Voltage Control - Wolfs, Peter; Thomas, P. (Victoria University, 2006)
Single phase rectifiers with power factor correction circuits based on the boost converter find broad application in consumer equipment. A fundamental design difficultly is caused by the need to trade off the input line current wave shape and the dynamic response of the output energy storage capacitor voltage regulation loop. The energy balance requirement inherent in single phase systems forces a significant 100Hz voltage ripple on the output capacitor. A high bandwidth voltage regulation loop will feed back enough of the 100Hz component to distort the current reference signals for the inner current control loop distorting the line wave shape. A reference model can be used to construct a ripple free estimate of the capacitor voltage. This paper shows that improved output capacitor voltage regulation can be achieve simultaneously with a high quality input current spectrum.